2023
DOI: 10.33158/asb.r194.v10.2024
|View full text |Cite
|
Sign up to set email alerts
|

Initial growth and chlorophyll indices of maize plants originating from seeds of different shapes and sizes

Lucian Alex Santos,
Benhur Schwartz Barbosa,
Carolina Cipriano Pinto
et al.

Abstract: The objective of this work was to evaluate the initial growth and chlorophyll content of maize plants originated from seeds with different sizes and shapes, as well as to establish the relationship between growth traits, chlorophyll index and seed formats. The experimental design was a randomized complete blocks, and the treatments were composed by seeds of four sizes and shapes for each of the two genotype used, and four collection periods (21, 24, 27 and 30 DAE) and four replications. The root and shoot leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Important researches have been done with grasses (Karasawa et al, 2023;Treter et al, 2023;Fracchinello et al, 2023;Santos et al, 2024). Studies conducted by Laudien, Schauberger, Makowski and Gornott (2020) revealed that extreme weather events have significantly negative impacts on maize grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…Important researches have been done with grasses (Karasawa et al, 2023;Treter et al, 2023;Fracchinello et al, 2023;Santos et al, 2024). Studies conducted by Laudien, Schauberger, Makowski and Gornott (2020) revealed that extreme weather events have significantly negative impacts on maize grain yield.…”
Section: Introductionmentioning
confidence: 99%